Comprehensive Thermal Characteristic Investigations on Hemp- and Jute-Based Nature Fibre-Reinforced Composites for Engineering Applications through Coupled and Verified Engineering Approaches - Sabari Thangavel; Mohamed Aashik Jaffar Ali; Raj Kumar Gnanasekaran; Beena Stanislaus Arputharaj; Arunkumar Karuppasamy; Hussein A. Z. AL-Bonsrulah; Parvathy Rajendran; Vijayanandh Raja; Devendhiran Soundararajan; Krishnakumar Kalaivani Muthuramalingam (Journal of Engineering)
Natural fibre-reinforced polymer composites (NFRPs) have gained increasing attention in recent years as an alternative to conventional materials such as steel and aluminum alloys due to their ecofriendly, renewable, and low-cost nature. This paper focuses on the thermal application of NFRPs, which have shown great potential due to their good thermal insulation properties. In this study, the fabrication of jute and hemp fibre-reinforced composites, experimental testing, comparison, validation by using computational method, and proposed hemp NFRPs insulated exhaust pipe in place of conventional steel pipe. However, challenges such as moisture absorption and limited thermal properties on high thermal load still need to be addressed to enable the full-scale commercialization of NFRPs in thermal applications. For these comprehensive investigations, coupled and verified engineering approaches have been imposed. Fluid-thermal coupling has been executed in ANSYS workbench associated with conventional test outcomes. Through this approach, the low weight and low cost-based thermal load resisting material has been proposed for various engineering applications.